Total Alpha activity and Radon-222 activity in the underground water of some regions of Ukraine (Environment & Health, 2021)
Objective: We aimed to analyze the results of the measurements of the total alpha activity and activity of radon-222 in the water of artesian wells to establish the geographical regions of Ukraine which require a deep attention to the assessment of the radioactivity of the groundwater.Methods: We used empirical, analytical, radiometric, spectrometric methods and method of mathematical statistics in the study.Materials: We carried out a statistical analysis of the results of the measurements of the total alpha activity and the activity of radon-222 in water samples from the artesian wells of 23 administrative regions of Ukraine studied during 2016 - 2020.Results: Analysis of the results of the measurements of the total alpha-activity and radon-222 activity in the water of artesian wells showed their significant heterogeneity for different regions of Ukraine and a connection with the geological features of the area. The statistical distribution of the values of the total alpha activity and the activity of radon-222 in water samples, diagrams of the range of measured values within the regions of Ukraine and between regions are presented in the work; the measurement results were plotted on the hydrogeological map of Ukraine.Conclusion: The values of the total alpha activity and the activity of radon-222 indicate that these indicators are extremely heterogeneous for the territory of Ukraine and reflect the geological features of the area. The results of the analysis can be useful for making recommendations to collective and individual water consumers, well owners regarding the need in more detailed study of the content of natural radionuclides in the sources of water and the use of the appropriate methods of water treatment in cases of non-compliance with the accepted standards. It is shown that it is necessary to develop a strategy for radiation monitoring of the groundwater quality in the country in order to study objectively the existing state and the achievement of an acceptable quality of the water consumed by the population.
Keywords: drinking water; radionuclides; total alpha activity; radon-222; individual dose criterion